The Comparison of Adjective in Indonesian, Javanese, and Sundanese Languages: a Syntactic Typology Analysis - Tri Pujiati (English Department - University of Sultan Ageng Tirtayasa, 2017)
The main focus of this study is to describe the order of degree word and adjective (AdjDeg) or (DegAdj) in three languages; Indonesian, Javanese, and Sundanese. Specifically, the study looks at the similarities and differences of typological syntactic features in three languages. This research used descriptive qualitative research by using data which belong to Austronesian language families. The results showed that (1) the similarities and differences of the order of modifying phrase in Indonesian, Javanese, and Sundanese which have different features in order of word degree and adjective, some of the compositions are (AdjDeg), or (DegAdj), and both of them; (2) the similarities at the level of comparison, the composition that often occur is ‘lebih + adjective+ dari’ in Indonesian language, ‘luweh + adjective + soko’ in Javanese language, or ‘leuwih + adjective + ti’ in Sundanese language; (3) at the level of superlative, the similarities of order of degree word in Indonesian language is ‘paling + adjective’, Javanese is ‘subject + paleng+ adjective + soko + object’ , Sundanese is ‘subject + pohara + adjective + na + ti + object. The difference, In Indonesian ‘Subject + ter + adjective’, Javanese language ‘subject + paleng + adjective’, Sundanese language, ‘subject +pang + adjective + na’; (4) On equative level, the similarities of equative, Indonesian language is ‘Subject + sama + Adjective + nya’, Javanese language, ‘subject + podho + adjective + e’, Sundanese is ‘subject + sarua + adjective + na’. The differences, Indonesian language, ‘Subject + Se + adjective’, Javanese language, ‘subject + adjective + e + podho’, Sundanese ‘subject + adjective + na + sarua’. This research can be used as a reference in advanced research related to the typology in order of degree word and adjective with data from different language in Indonesian archipelago. Keywords : Syntactic Typology, Comparative, Superlative, and Equative